2017
DOI: 10.1016/j.joi.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on the skewness patterns and fractal nature of research productivity distributions at field and discipline level

Abstract: The paper provides an empirical examination of how research productivity distributions differ across scientific fields and disciplines. Productivity is measured using the FSS indicator, which embeds both quantity and impact of output. The population studied consists of over 31,000 scientists in 180 fields (10 aggregate disciplines) of a national research system. The Characteristic Scores and Scale technique is used to investigate the distribution patterns for the different fields and disciplines. Research prod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…This result is consistent with recent findings by Yair et al ( 2017 : 5) who showed in a sample of Israel Prize laureates that the tail of excellence may behave as the entire productivity distribution. In a similar vein, Abramo et al ( 2017a : 334) found the same pattern in the Italian national research system: “research productivity distribution for all fields is highly skewed to the right, both at overall level and within the upper tail”. This is also the case in Poland.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This result is consistent with recent findings by Yair et al ( 2017 : 5) who showed in a sample of Israel Prize laureates that the tail of excellence may behave as the entire productivity distribution. In a similar vein, Abramo et al ( 2017a : 334) found the same pattern in the Italian national research system: “research productivity distribution for all fields is highly skewed to the right, both at overall level and within the upper tail”. This is also the case in Poland.…”
Section: Discussionmentioning
confidence: 66%
“…Instead, it follows a Paretian (power law) distribution (O’Boyle and Aguinis 2012 ). Distributions of different social phenomena—such as income, wealth, and prices—show “strong skewness with long tail on the right, implying inequality” (Abramo et al 2017a : 324). Academic knowledge production is not an exception because unproductive scientists work alongside ‘top researchers’ in academic units, universities, and national systems (Abramo et al 2013 ; Piro et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result is consistent with recent findings by Yair et al (, p. 5), who showed that, in a sample of Israel Prize laureates, the tail of excellence may behave like the overall productivity distribution. Abramo et al identified the same pattern in the Italian national research system: ‘research productivity distribution for all fields is highly skewed to the right, both at overall level and within the upper tail’ (, p. 334), and this is the case right across Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than a Gaussian (normal) distribution, individual performance in science tends to follow a Paretian (power law) distribution (O'Boyle & Aguinis, ). In general, social phenomena such as income, wealth and price show ‘strong skewness with long tail on the right, implying inequality’ (Abramo, D'Angelo, & Soldatenkova, , p. 324), and academic knowledge production is no exception (Kwiek, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…CSS involves subdividing a population into classes on the basis of the distribution of a given variable. The CSS technique was developed by Schubert, Glänzel, and Braun (1987) and has been applied in many bibliometric studies (Glänzel & Schubert, 1988;Glänzel, 2011;Ruiz-Castillo & Costas, 2014;Abramo, D'Angelo, & Soldatenkova, 2017;Bornmann & Glänzel, 2017) for classification of the given unit (publications, journals, individual scientists, research groups, institutions, etc. ), in function of the value of the bibliometric indicator measured on those units.…”
Section: The Characteristic Scores and Scales Methodsmentioning
confidence: 99%